The Impact of Student Responses and Concepts Understanding on the Environmental Care Character of Elementary School Students - Ramli, Supian; Novanda, Ramazani; Sobri, Muhammad; Triani, Elza (International Journal of Elementary Education, 2022)
The importance of caring for the environment is owned by each individual from an early age, making research on how the effect of student responses on the character of caring for the environment in the tribe and understanding of students' concepts in thematic learning of our 8 themes of the environment of friends on the character of caring for the environment of students needs to be done. This study aims to examine the effect of student responses on the environmental care character of the inner tribe and students' conceptual understanding of the environmental care character of elementary school students. This type of research uses a mixed method of explanatory sequential design. The subjects of this study were 5th grade elementary school students. The sampling technique was simple random sampling. The number of samples is 100 students. The research instrument is in the form of response questionnaires and questions as well as interviews with data analysis using statistics and Miles and Huberman. The results showed that students' understanding of concepts in thematic learning themed 8 was environmentally friendly and students' responses to the environmental care character of ethnic children in influencing the environmental care character of elementary school students. So that knowledge about caring for the environment of students greatly affects the improvement of the character of caring for the environment of students.